2012
DOI: 10.1016/j.neuroimage.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

MRI signature in a novel mouse model of genetically induced adult oligodendrocyte cell death

Abstract: Two general pathological processes contribute to multiple sclerosis (MS): acute inflammation and degeneration. While magnetic resonance imaging (MRI) is highly sensitive in detecting abnormalities related to acute inflammation both clinically and in animal models of experimental autoimmune encephalomyelitis (EAE), the correlation of these readouts with acute and future disabilities has been found rather weak. This illustrates the need for imaging techniques addressing neurodegenerative processes associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
5
7
0
Order By: Relevance
“…MTR correlates significantly with the degree of myelination as shown in postmortem tissue of MS patients (Schmierer et al, 2004 ). The decline in MTR that was observed in the oligodendrogliopathy model with the aid of the CryoProbe (Figure 6B ) could be corroborated with evidence of white matter pathology upon histological analysis (Figure 6C ; Mueggler et al, 2012 ).…”
Section: Neurovascular Applicationssupporting
confidence: 54%
See 1 more Smart Citation
“…MTR correlates significantly with the degree of myelination as shown in postmortem tissue of MS patients (Schmierer et al, 2004 ). The decline in MTR that was observed in the oligodendrogliopathy model with the aid of the CryoProbe (Figure 6B ) could be corroborated with evidence of white matter pathology upon histological analysis (Figure 6C ; Mueggler et al, 2012 ).…”
Section: Neurovascular Applicationssupporting
confidence: 54%
“…For instance transgenic models involving suicide genes that induce oligodendrogliopathy are powerful tools for studying non-inflammatory demyelination and remyelination (Traka et al, 2010 ; Pohl et al, 2011 ). Using a cryogenically-cooled RF coil, pronounced T 2 hyperintensities were revealed in brain stem and cerebellar structures of this model (Figure 6A ); these changes were accompanied with a decreased magnetization transfer ratio (MTR; Figure 6B ; Mueggler et al, 2012 ). MTR reflects the exchange of magnetization between pools of differently mobilized protons (Wolff and Balaban, 1989 ), commonly a rather freely mobile pool and a rather immobile pool associated with macromolecules, such as in axonal membranes or myelin (Alonso-Ortiz et al, 2015 ).…”
Section: Neurovascular Applicationsmentioning
confidence: 77%
“…For example, a small functional MRI study showed that obesity was associated with reductions in brain activity during the performance of a demanding working memory task and that the strongest predictor of reduced activation was not higher BMI but lower insulin sensitivity (18). In addition, inflammatory pathways have been implicated in white matter atrophy in both humans (40) and animal models (41) and also increase with obesity. Neuropsychological studies have suggested that some cognitive domains supported by these same brain areas are compromised in obesity (e.g., planning and mental flexibility, problem solving, memory, psychomotor speed (42–45)).…”
Section: Discussionmentioning
confidence: 99%
“…The stronger decrease is thought to be due to axonal swelling, cellular infiltration and edema (Boretius et al, 2012). In mice with EAE induced by proteolipid protein, a decrease in MTR was seen in brainstem, cerebellum and frontal cortex, but not olfactory bulb (Mueggler et al, 2012). In a study of the effect of glatiramer acetate (GA) on EAE mice, the untreated EAE mice are shown to have lower MTR values than the GA treated (Aharoni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%